2007
DOI: 10.1111/j.1365-2036.2007.03438.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of peptic ulcer in uraemic and non‐uraemic patients after Helicobacter pylori eradication: a 2‐year study

Abstract: SUMMARY BackgroundThe role of Helicobacter pylori in the pathogenesis of peptic ulcer disease in patients with uraemia remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 26 publications
2
57
2
Order By: Relevance
“…Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB. In addition, H. pylori infection has been associated with a higher risk of UGIB (23,24), and H. pylori eradication therapy decreases the risk of recurrent UGIB (25). Forty-two (1.4%) patients were receiving H. pylori eradication therapy; this therapy did not significantly affect UGIB risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB. In addition, H. pylori infection has been associated with a higher risk of UGIB (23,24), and H. pylori eradication therapy decreases the risk of recurrent UGIB (25). Forty-two (1.4%) patients were receiving H. pylori eradication therapy; this therapy did not significantly affect UGIB risk.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is required to confirm whether hypoalbuminemia patients have a higher risk of developing non-H. pylori and non-NSAID peptic ulcers, as do other comorbidities, such as liver cirrhosis, malignancy, and ESRD [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ESRD exhibit a higher incidence of PUD than do patients without renal disease [12] . H. pylori is critical in the development of peptic ulcers [46] .…”
Section: H Pylori Eradication and Recurrent Peptic Ulcers In Patientmentioning
confidence: 99%
“…Studies on H. pylori infections in uremic patients have reported rates varying from 27% to 73.0% [12][13][14][15][16][17][18][19][20] . This variation may have been caused by small sample sizes, nonuniform duration of dialysis, and varying methodologies and enrollment criteria.…”
Section: H Pylori Prevalence Among Patients With End-stage Renal Dismentioning
confidence: 99%
See 1 more Smart Citation